Some results on the space of holomorphic functions taking their values in b-spaces - Belghiti, M. T.; Aqzzouz, B.; Elalj, H.; Nouira, R. (Methods of Functional Analysis and Topology, 2006)
We define a space of holomorphic functions O_1(U,E/F), where U is an open pseudo-convex subset of C^n, E is a b-space and F is a bornologically closed subspace of E, and we prove that the b-spaces O_1(U,E/F) and O(U,E)/O(U,F) are isomorphic.